A systematic review of physiological reactivity to stimuli in autism. (1st November 2016) - Lydon, Sinéad; Healy, Olive; Reed, Phil; Mulhern, Teresa; Hughes, Brian M.; Goodwin, Matthew S.
Abstract: Objective : The prevalence of abnormal behavioural responses to a variety of stimuli among individuals with autism has led researchers to examine whether physiological reactivity (PR) is typical in this population. This article reviewed studies assessing PR to sensory, social and emotional, and stressor stimuli in individuals with autism. Methods : Systematic searches of electronic databases identified 57 studies that met our inclusion criteria. Studies were analysed to determine: (a) participant characteristics; (b) physiological measures used; (c) PR to sensory, social and emotional or stressor stimuli; (d) the relation between PR and behavioural or psychological variables and (e) baseline physiological activity. A novel measure of methodological quality suitable for use with non-randomized, non-interventional, psychophysiological studies was also developed and applied. Results : Individuals with autism were found to respond differently than typically developing controls in 78.6%, 66.7% and 71.4% of sensory, social and emotional, and stressor stimulus classes, respectively. However, this extant literature is characterized by variable and inconsistent findings, which do not appear to be accounted for by varying methodological quality, making it difficult to determine what specific factors differentiate individuals with autism who present with atypical PR from those who do not. Conclusions : Despite this uncertainty, individual differences in PR are clearly present in autism, suggesting additional research is needed to determine the variables relating to PR among those with ASD and to examine the possible existence of physiological subtype responders in the population.